Oil Price and Stock Return: Evidence of Mining Companies in Indonesia - Endri, Endri; Rinaldi, Muhamad; Arifian, Dini; Saing, Bungaran; Aminudin, Aminudin (International Journal of Energy Economics and Policy, 2021)
This research aims to analyze the determinants of stock return disclosure of mining sector companies listed on the Indonesia Stock Exchange in 2014-2018. The research adopted the Eviews program in data processing and Random effect regression model was chosen to test the relationship between internal and external indicators as independent variables include Return On Asset (ROA), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Oil Price and Exchange Rate. The result shows that Return on Assets and Debt to Equity Ratio have no effect on stock return. Total Asset Turnover and Exchange Rate have negative and significant effect on stock return, while Oil price have positif and significant effect on stock return. Keywords: Stock Return, Return on Assets, Debt to Equity Ratio, Total Asset Turnover, Oil Price, Exchange Rate. JEL Classifications: E22, E44, G11 DOI: https://doi.org/10.32479/ijeep.10608